6-Substituted 2-azabicyclo[2.2.1]hept-5-enes by nitrogen-directed radical rearrangement: Synthesis of an epibatidine analogue with high binding affinity at the nicotinic acetylcholine receptor - Hodgson, D; Maxwell, C; Wisedale, R; Matthews, I; Carpenter, K; Dickenson, A; Wonnacott, S (2001)
Base-induced isomerisation of epoxide 13 gives an azanortricyclanol 17 which is a precursor for a novel free-radical induced rearrangement to 6-substituted 2-azabicyclo[2.2.1]hept-5-enes 28-31. Compound 31 undergoes selective exo-face hydrogenation to give the 6-substituted 2-azabicyclo[2.2.1]heptane 33 (structure confirmed by X-ray crystallographic analysis). Deprotection of 33 gives epibatidine analogue 2 which has been shown to bind with high affinity at rat brain nicotinic acetylcholine receptors.